Empathy: : past, present and future perspectives - Bach, Albert K. (Nova Science Publishers, 2019)
"In this compilation, the authors analyze the feeling of empathy in the context of the constitution of empathetic bonds that mark human relations. Empathy is shown as a spontaneous manifestation, natural and implicit, and present in all human encounters. Following this, the connection between the capacity for empathy and basic personality traits and affective attachment dimensions is investigated, seeking to determine which personality type is most empathetic. The concept of intracultural empathy as a culturally-relevant manifestation of empathy that is directed toward members of a shared cultural/ethnic/racial group is introduced, and its utility for understanding the particular cultural context of critical consciousness development among African American youth is explored. One study utilizes a large sample of college students to examine the relationship between cyberbullying participation roles (cyberbullies, cybervictims, cyberbully-victims, and non-participant controls), empathy (cognitive and affective), and psychopathy (primary and secondary). The work also examines these relationships by gender to identify whether male and female differences exist among cyberbullies, cybervictims and cyberbully-victims across these traits. Next, a study is presented which seeks to confirm or refute the assumption that a program of empathy development in pre-gradual teachers training has a positive effect on changes in cognitive and emotional element of empathy in an experimental group of future teachers. The authors go on to explore the concept of empathy in physical education and sport from a diachronic perspective. Additionally, activities for providing empathy skills through physical education and sports are described. The experience of awe in relation to the empathic 'feeling into" and the ''being moved' phenomenological quality of aesthetic experience is investigated, as instantiated in the specific case of religious icons-paintings. This approach focuses specifically on an extensive exploration of the perceivers' experience of religious icons in relation to any emergent aesthetic, cultural, spiritual and religious issues. Lastly, different perspectives on animal rights activities are discussed in conjunction with the role that sympathy and empathy play. The authors then move on to look at the dualism and anti-dualism aspects of support in detail, as well as the theoretical contributions made to understanding why views of collective action relying on economic rationality are inadequate in explaining human behavior"-- Provided by publisher.
Keywords: Empathy.; Empathy; Empathie.; empathy.